(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The Russian government’s attempts to explore and study the Central Asian khanates began in the early 18th century, during the reign of Peter the Great, when the Khanate of Khiva became the object of Russia’s close attention.